Erythropoietin Reduces Neuronal Cell Death and Hyperalgesia Induced by Peripheral Inflammatory Pain in Neonatal Rats. Issue 1 (21st July 2011) - Mohamad, Osama; Chen, Dongdong; Zhang, Lingling; Hofmann, Cane; Wei, Ling; Yu, Shan Ping
Painful stimuli during neonatal stage may affect brain development and contribute to abnormal behaviors in adulthood. Very few specific therapies are available for this developmental disorder. A better understanding of the mechanisms and consequences of painful stimuli during the neonatal period is essential for the development of effective therapies. In this study, we examined brain reactions in a neonatal rat model of peripheral inflammatory pain. We focused on the inflammatory insult-induced brain responses and delayed changes in behavior and pain sensation. Postnatal day 3 pups received formalin injections into the paws once a day for 3 days. The insult induced dysregulation of several inflammatory factors in the brain and caused selective neuronal cell death in the cortex, hippocampus and hypothalamus. On postnatal day 21, rats that received the inflammatory nociceptive insult exhibited increased local cerebral blood flow in the somatosensory cortex, hyperalgesia, and decreased exploratory behaviors. Based on these observations, we tested recombinant human erythropoietin (rhEPO) as a potential treatment to prevent the inflammatory pain-induced changes. rhEPO treatment (5, 000 U/kg/day, i.p.), coupled to formalin injections, ameliorated neuronal cell death and normalized the inflammatory response. Rats that received formalin plus rhEPO exhibited normal levels of cerebral blood flow, pain sensitivity and exploratory behavior. Treatment with rhEPO also restored normal brain and body weights that were reduced in the formalin group. These data suggest that severe inflammatory pain has adverse effects on brain development and rhEPO may be a possible therapy for the prevention and treatment of this developmental disorder.